Building a Culture of Academic Integrity through Restorative Justice - Abramson, Alana; Rucker, Anna (Canadian Perspectives on Academic Integrity, 2023)
Restorative justice (RJ) is a philosophy and set of values and principles that can inform justice practices and responses to harm. Its processes aim to address needs, repair or transform relationships, and promote understanding, meaningful dialogue, and direct accountability. Ethical and mindful approaches to RJ processes have the potential to address power imbalances, enhance community participation, establish relationship-based environments, and respond more meaningfully to human needs, which promotes social justice. A restorative lens has been applied to post-secondary environments in relation to academic and non-academic harms that occur on and off campus between students, faculty, and staff. This workshop will describe what we are learning through taking a restorative approach to building a culture of academic integrtity at Kwantlen Polytechnic University. Workshop participants can expect us to cover the following topics: * Describe the principles and procedures of restorative justice in relation to promoting a culture of academic integrity * Identify the benefits of restorative justice as an effective response to academic integrity violations compared to punitive approaches